2005
DOI: 10.1002/art.21406
|View full text |Cite
|
Sign up to set email alerts
|

Hip abduction moment and protection against medial tibiofemoral osteoarthritis progression

Abstract: Objective. To test the hypothesis that a greater peak internal hip abduction moment is associated with a reduced likelihood of ipsilateral medial tibiofemoral osteoarthritis (OA) progression.Methods. Fifty-seven persons with knee OA (by definite osteophyte presence and symptoms) were evaluated. Baseline assessments included kinematic and kinetic gait parameters, obtained with an optoelectronic camera system and force platform, with inverse dynamics used to calculate 3-dimensional moments at the joints; pain, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
197
7
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(246 citation statements)
references
References 20 publications
(20 reference statements)
19
197
7
12
Order By: Relevance
“…Recent studies have reported differences in hip moments between those with and without knee OA (11) and between those who are and are not on a surgical waitlist (15), and support the earlier findings of Chang et al (12). In particular, those with greater disease severity exhibited lower external hip adduction moments and increased external hip abduction moments.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Recent studies have reported differences in hip moments between those with and without knee OA (11) and between those who are and are not on a surgical waitlist (15), and support the earlier findings of Chang et al (12). In particular, those with greater disease severity exhibited lower external hip adduction moments and increased external hip abduction moments.…”
Section: Introductionsupporting
confidence: 73%
“…In particular, biomechanics at the hip, pelvis, and trunk have all been shown to affect dynamic joint loading at the knee (11)(12)(13)(14). The importance of these proximal joints is highlighted by findings from Chang et al (12), which showed that increased internal hip abduction moments (equivalent to external hip adduction moments) attributed to higher hip abduction strength were protective against OA progression in the knee over an 18-month period. Accord-ingly, the focus has shifted from solely examining changes at the knee during walking in those with knee OA to understanding factors that influence proximal gait mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…In the MAK cohort, greater internal hip abduction moment during gait protected against medial tibiofemoral OA progression (14), suggesting that biomechanical factors at the knee and hip may interact. However, thigh rotation was not related to knee adduction during gait with toes out (20), implying a limited effect on the hip.…”
Section: Introductionmentioning
confidence: 95%
“…The ground reaction force (GRF) heavily influences knee-joint load. 15 Internal net hip-, knee-, and ankle-joint moments (ie, the net joint torques that are produced by internal structures such as muscles) also influence knee-joint load; eg, the net internal hip extension, 16 hip abduction, 17,18 knee extension, 19 plantar flexion, 19 and overall support moment 20 (the algebraic sum of the hipextension, knee-extension, and plantar-flexion moments) each contribute to vertical GRF and the corresponding tibiofemoral joint load. Peak external knee-adduction torque has also been associated with knee-joint load.…”
mentioning
confidence: 99%